Kaempferol Promotes Apoptosis While Inhibiting Cell Proliferation via Androgen-Dependent Pathway and Suppressing Vasculogenic Mimicry and Invasion in Prostate Cancer - Jun Da; Mingxi Xu; Yiwei Wang; Wenfeng Li; Mujun Lu; Zhong Wang (Analytical Cellular Pathology)
Kaempferol is a well-known natural flavonol reported to be a potential treatment for multiple cancers. In this study, we demonstrated that cell growth of androgen-sensitive LNCaP cells could be inhibited 33% by 5 μM kaempferol, around 60% by 10 μM kaempferol, and almost 100% by 15 μM kaempferol. Also, kaempferol showed relatively limited effect on PC-3 cells and nonmalignant RWPE-1 cells. In the presence of DHT, the IC50 for kaempferol was 28.8±1.5 μM in LNCaP cells, 58.3±3.5 μM in PC-3 cells, and 69.1±1.2 μM in RWPE-1 cells, respectively. Kaempferol promotes apoptosis of LNCaP cells in a dose-dependent manner in the presence of dihydrotestosterone (DHT). Then, luciferase assay data showed that kaempferol could inhibit the activation of androgen receptors induced by DHT significantly. The downstream targets of androgen receptors, such as PSA, TMPRSS2, and TMEPA1, were found decreased in the presence of kaempferol in qPCR data. It was then confirmed that the protein level of PSA was decreased. Kaempferol inhibits AR protein expression and nuclear accumulation. Kaempferol suppressed vasculogenic mimicry of PC-3 cells in an in vitro study. In conclusion, kaempferol is a promising therapeutic candidate for treatment of prostate cancer, where the androgen signaling pathway as well as vasculogenic mimicry are involved.